Utvärdering av viabilitet hos selekterad hingstsperma med hjälp av fluorometri - Björk, Hanna (SLU/Dept. of Anatomy, Physiology and Biochemistry (until 231231), 2008)
There is considerable variation between stallions in semen quality and fertility due to the fact that selection of stallions for breeding is not based on fertility or semen quality but on performance. The increasing use of cooled semen for artificial insemination has resulted in decreasing pregnancy rates. Therefore the equine breeding industry needs new methods for evaluation and development of sperm quality and fertility. This study is a part of such a project and is performed by SLU in cooperation with Flyinge AB. Ten stallions at the Flyinge National Stud were used in the study and three ejaculates were collected from each stallion. The ejaculates were analyzed ten times under different conditions, such as time, storing temperature and with/without selection. The selection was carried out by Single Layer Centrifugation. The method for analysis of the spermatozoa was computerized fluorometry of Hoechst 33258-stained semen samples. The objective of the study was to: